Evaluation of the Implementation of the Detailed Spatial Plan (RDTR) 2012-2032 in Jagakarsa District: A Perspective on Land Use Suitability and Regional Functional Alignment - Aindyana, Hernata; Taryana, Didik; Damayanti, Astrid (Jurnal Planologi, 2025)
ABSTRACTSpatial planning is a crucial aspect of sustainable regional management, particularly in urban areas with high mobility, such as Jagakarsa District, South Jakarta. As a buffer zone and water catchment area for Jakarta, Jagakarsa faces the challenge of land-use conversion due to high population density (15,090 people/km²) and increasing economic activity. This study aims to evaluate the implementation of the Detailed Spatial Plan (RDTR) 2012-2032 in Jagakarsa through a quantitative spatial approach using the overlay technique on RDTR maps and on-screen digitization of 2024 land use based on Google Earth imagery.The research method involves land use suitability variables based on the ITBX matrix, with data validation using Confusion Matrix and Kappa Coefficient, achieving 86% accuracy (Google Earth) and 95% (BPN). Data collection was conducted through manual digitizing, followed by spatial analysis to measure the suitability of RDTR implementation against existing land use. The study's benefit is to provide targeted spatial planning policy recommendations, particularly in protecting the ecological function of the region. The results indicate an RDTR implementation suitability rate of 91.97%, with the highest non-compliance found in horticulture sub-zones (69.51%), cemeteries (71.13%), water bodies (40.15%), and green open spaces (21.75%). Although RDTR designates Jagakarsa as a water catchment area, the green open space (RTH) coverage only reaches 13%, which is far below the 30% standard mandated by Law No. 26 of 2007. Proposed solutions include increasing RTH allocation to 20%, strict monitoring of my land-use changes, and enforcing Building Permit (IMB) regulations to restore Jagakarsa's ecological role as a natural flood control barrier. These steps are expected to create a healthy and sustainable environment, achieving a balance between development needs and environmental conservation. Keywords:  RDTR, Land Use, Suitability, Jagakarsa